APAKAH STRUKTUR DEWAN KOMISARIS BERPENGARUH TERHADAP KINERJA PERUSAHAAN? - Y Anni Aryani; Isna Putri Rahmawati; Doddy Setiawan (Universitas Mercu Buana, 2018)
This research aims at examining the effect of board of commissioners structure on firm performance using Indonesian context. We investigate the effectiveness of three characteristics of board of commissioners including percentage of independent commissioners, percentage of woman in board of commissioners and size. Sample of the study consists of firm listed in Jakarta Islamic Index during 2006 – 2016 periods. There are 258 firm-years as sample of the study. The result of the study shows that percentage of independent commissioners and percentage of woman in board of commissioner have significant effect on firm performance. On the other hand, board of commissioners size have no significant effect on firm performance. The study provide evidence that independent commissioner have positive effect to increase firm performance. Independent commissioners push firm to achieve higher level of performance. However, woman commissioners negatively affect firm performance. Thus, woman commissioners might not have provide better monitoring activity to push firm performance